2010
DOI: 10.1038/cr.2010.92
|View full text |Cite
|
Sign up to set email alerts
|

Proto-oncogenic H-Ras, K-Ras, and N-Ras are involved in muscle differentiation via phosphatidylinositol 3-kinase

Abstract: Oncogenic H-Ras G12V and its variants have been shown to inhibit muscle differentiation. However, the role of proto-oncogenic Ras (c-Ras) in muscle differentiation remains unclear. The active GTP-bound form of Ras has been known to associate with diverse effectors including Raf, phosphatidylinositol 3-kinase (PI3K), Ral-GDS, and other molecules to transmit downstream signals. We hypothesize that c-Ras may stimulate muscle differentiation by selectively activating PI3K, an important mediator for muscle differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 56 publications
1
22
0
Order By: Relevance
“…A recent study revealed that oncogenic mutated H-Ras G12V inhibits muscle differentiation44. If H-Ras is involved in DM pathology, it may help us to better understand DM1.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study revealed that oncogenic mutated H-Ras G12V inhibits muscle differentiation44. If H-Ras is involved in DM pathology, it may help us to better understand DM1.…”
Section: Discussionmentioning
confidence: 99%
“…Nuclear extracts were obtained, according to a previous report, with minor modifications (25). Briefly, confluent cells in 10-cm-diame ter dishes were resuspended in 200 μl of buffer (10 mM HEPES, pH 7.9, 10 mM KCl, 1 mM DTT, 0.5 mM EDTA, 0.5 mM PMSF), and lysed with 12.5 μl of 10% NP-40.…”
Section: Methodsmentioning
confidence: 99%
“…The intracellular ROS and mitochondrial membrane potential were measured using flow cytometry as previously described [29,30,32]. In brief, equal numbers of RINm5F cells were seeded in a 6-well microplate and grown to 80% confluency in RPMI medium.…”
Section: Analysis Of Intracellular Ros and Mitochondrial Membrane Potmentioning
confidence: 99%